Effects of Barnett Magnetic Dipole–Dipole Interaction on Grain Growth and Destruction - Thiem Hoang; Bao Truong (The Astrophysical Journal, 2023)
Rapidly spinning magnetic grains can acquire large magnetic dipole moments due to the Barnett effect. Here we study the new effect of Barnett magnetic dipole–dipole interaction on grain–grain collisions and grain growth, assuming that grains are spun up by radiative torques. For the ideal situation in which grains have parallel Barnett dipole moments aligned with the ambient magnetic field, we find that the collision rate between grains having embedded iron inclusions can be significantly enhanced due to Barnett magnetic dipole–dipole interaction when grains rotate suprathermally by radiative torques. We discuss the implications of enhanced collision rate for grain growth and destruction in the circumstellar envelope of evolved stars, photodissociation regions, and protostellar environments. Our results first reveal the potential importance of the dust magnetic properties, magnetic fields, and the local radiation field for grain growth and destruction. Detailed numerical simulations of grain dynamics that take into account the variation of Barnett dipoles and grain alignment are required to quantify the exact role of Barnett dipole–dipole interaction in grain evolution.